Social Networking Sites Use and Cross Cultural Adaptation of Muslim Indonesian Students in Australian Universities: Valuing Cultural Diversity - Imam Nuraryo (Jurnal Komunikasi)
Muslim Asian students have diverse specific needs when undertaking education in western country universities. Many international students use social networking sites as media for distance communication and helping in their adjustment.